2013
DOI: 10.4047/jap.2013.5.3.241
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of various metal oxides on mechanical and physical properties of heat-cured polymethyl methacrylate denture base resins

Abstract: PURPOSETo evaluate the effect of various metal oxides on impact strength (IS), fracture toughness (FT), water sorption (WSP) and solubility (WSL) of heat-cured acrylic resin.MATERIALS AND METHODSFifty acrylic resin specimens were fabricated for each test and divided into five groups. Group 1 was the control group and Group 2, 3, 4 and 5 (test groups) included a mixture of 1% TiO2 and 1% ZrO2, 2% Al2O3, 2% TiO2, and 2% ZrO2 by volume, respectively. Rectangular unnotched specimens (50 mm × 6.0 mm × 4.0 mm) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
191
1
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(214 citation statements)
references
References 29 publications
9
191
1
13
Order By: Relevance
“…25,[30][31][32][33] In addition, reinforcing PMMA with aluminum increased the flexural strength, impact strength, tensile strength, compressive strength, and surface hardness of the resin. 26,30,32,34 Warpage also decreased significantly after addition of aluminum to PMMA. On the other hand, some studies found that adding aluminum decreases both the impact and tensile strength of PMMA.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…25,[30][31][32][33] In addition, reinforcing PMMA with aluminum increased the flexural strength, impact strength, tensile strength, compressive strength, and surface hardness of the resin. 26,30,32,34 Warpage also decreased significantly after addition of aluminum to PMMA. On the other hand, some studies found that adding aluminum decreases both the impact and tensile strength of PMMA.…”
mentioning
confidence: 88%
“…Consequently, better food sensation and healthier oral mucosa were expected by adding metal fillers to denture base resin. [25][26][27] Recently, the incorporation of nanofillers (Table 2) has been suggested to improve PMMA properties. The high surface area, fine size, and homogenous distribution of nanofillers improved the thermal properties of PMMA and increased its thermal stability compared with pure PMMA.…”
Section: Fillersmentioning
confidence: 99%
See 2 more Smart Citations
“…[18][19][20][21] Zirconia (ZrO 2 ) is a metal oxide that has been widely used because it possesses high mechanical strength, good surface properties, and good biocompatibility and biological properties, thus making it a beneficial material for use in dental materials, such as reinforcement of denture bases and repair. [22][23][24][25] The incorporation of zirconia nanoparticles (nano-ZrO 2 ) into PMMA has been suggested to improve PMMA properties. 26,27 The addition of nano-ZrO 2 to PMMA significantly improves flexural strength and impact strength.…”
Section: Gad Et Almentioning
confidence: 99%